2018
DOI: 10.1002/path.5055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of PALB2‐associated breast cancers

Abstract: PALB2 is established as the most clinically important moderate to high penetrance breast cancer predisposition gene after BRCA1 and BRCA2. Mutations in classical familial cancer predisposition genes are presumed to be recessive at the cellular level and therefore a second inactivating somatic mutation is required in the tumour tissue. However, from the limited data that exist, PALB2 may be an example of a cancer predisposition gene that does not conform to Knudson's 'two hit' paradigm. We conducted genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…While wild‐type PALB2 partly complemented PALB2 siRNA‐treated cells, PALB2 p.M296Nfs mutant did not rescue HRR capacity (Fig D). Furthermore, overexpression of PALB2 p.M296Nfs mutant led to a two‐fold reduction in mClover‐positive cells, demonstrating that PALB2 p.M296Nfs leads to HRR deficiency despite the presence of endogenous wild‐type PALB2, in favor of a dominant negative effect (Fig E; Lee et al , ). Collectively, both sequencing and functional assays indicate that HRR deficiency in PDX093 is due to the PALB2 c.886dupA mutation.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…While wild‐type PALB2 partly complemented PALB2 siRNA‐treated cells, PALB2 p.M296Nfs mutant did not rescue HRR capacity (Fig D). Furthermore, overexpression of PALB2 p.M296Nfs mutant led to a two‐fold reduction in mClover‐positive cells, demonstrating that PALB2 p.M296Nfs leads to HRR deficiency despite the presence of endogenous wild‐type PALB2, in favor of a dominant negative effect (Fig E; Lee et al , ). Collectively, both sequencing and functional assays indicate that HRR deficiency in PDX093 is due to the PALB2 c.886dupA mutation.…”
Section: Resultsmentioning
confidence: 89%
“…In these patients, the RAD51 assay could be used as an enrichment biomarker to better predict sensitivity to PARPi, since restoration of the HRR pathway might have occurred and result in PARPi resistance (Konstantinopoulos et al , ; Cruz et al , ). Second, tumors with somatic alterations in HRR‐related genes, such as the PALB2 mutations described in 4% of metastatic BC (Lefebvre et al , ; Lee et al , ). And third, tumors with epigenetic HRR silencing, such as BRCA1 promoter hypermethylation.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of pure IDP with sufficient DNA available (n = 9/24) were sequenced using a targeted gene panel (258 genes 27,29 ) (Supplementary Table 1) to identify driver somatic mutations (Fig. 3).…”
Section: Somatic Mutations In Idpmentioning
confidence: 99%
“…PALB2 , which is located on chromosome 16p12.1, is established as the third clinically important moderate-to-high penetrance breast cancer predisposition gene after BRCA1 and BRCA2 [2]. Many studies have reported the role of PALB2 polymorphisms in several loci with regard to breast cancer risk in the past decade, however with conflicting results [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%